A qualitative study exploring contextual challenges to surgical care provision in 21 LMICs. (27th April 2015) - Raykar, Nakul P; Yorlets, Rachel R; Liu, Charles; Greenberg, Sarah L M; Kotagal, Meera; Goldman, Roberta; Roy, Nobhojit; Meara, John G; Gillies, Rowan D
Abstract: Background: Billions of people worldwide are without access to safe, affordable, and timely surgical care. The Lancet Commission on Global Surgery (LCoGS) conducted a qualitative study to understand the contextual challenges to surgical care provision in low-income and middle-income countries (LMICs), and how providers overcome them. Methods: A semi-structured interview was administered to 143 care providers in 21 LMICs using stratified purposive sampling to include both urban and rural areas and reputational case selection to identify individual providers. Interviews were conducted in Argentina (n=5), Botswana (3), Brazil (10), Cape Verde (4), China (14), Colombia (4), Ecuador (6), Ethiopia (10), India (15), Indonesia (1), Mexico (9), Mongolia (4), Namibia (2), Pakistan (13), Peru (5), Philippines (1), Sierra Leone (11), Tanzania (5), Thailand (2), Uganda (9), and Zimbabwe (15). Local collaborators of LCoGS conducted interviews using a standardised implementation manual and interview guide. Questions revolved around challenges or barriers in the area of access to care for patients; challenges or barriers in the area of in-hospital care for patients; and challenges or barriers in the area of governance or health policy. De-identified interviews were coded and interpreted by an independent analyst. Findings: Providers across continent and context noted significant geographical, financial, and educational barriers to access. Surgical care provision in the rural hospital setting was hindered by a paucity of trained workforce, and inadequacies in basic infrastructure, equipment, supplies, and access to banked blood. In urban areas, providers face high patient volumes combined with staff shortages, minimal administrative support, and poor interhospital care coordination. At a policy level, providers identified regulations that were inconsistent with the realities of low-resource care provision (eg, a requirement to provide 'free' care to certain populations but without any guarantee for funding). Regional variation did exist on some matters, particularly related to prevalence of patient-provider mistrust and supply chain failures. Everywhere, providers have created innovative workarounds to overcome some of these barriers, such as clever financing mechanisms for planned surgery (eg, raising donated farm animals for cash in Zimbabwe, Ethiopia, and India), provision in scheduling and accommodations to facilitate patients from afar, reduction of cost and waste through re-sterilisation of disposable supplies, and locally sourcing consumables (eg, hand cleaning solution made of alcohol from the local distillery in India). Interpretation: Although some variation exists between countries, the challenges to surgical care provision are largely consistent and based on local resource availability; underfunded rural hospitals faced similar challenges worldwide. Global efforts to scale-up surgical services can focus on these commonalities (eg, investments in infrastructure, workforce), while local governments can tailor solutions to key contextual differences (eg, community-based outreach, supply chains, professional management, and interhospital coordination). Funding: None.